(untitled) (Perner’s Contacts, 2011)
Air Accident investigation should lead to uncovering the causes that precede the accident. The cause of every accident is a set of factors and sequence of events leading to its creation. During the investigation of air accidents is necessary to understand all these factors and sequence of events. Only in this case, the investigation of accidents has the impact on the safety of the aviation industry. Giving the right name to the causes, circumstances and sequence of events leads to the correct formulation of remedial actions and the creation of security defences. Only in this case, we can also consider building a predictive and proactive approach to safety. This article discusses the current approach to the investigation of aviation accidents and compares the current situation in the Czech Republic, the USA and Great Britain. This work was supported by the Grant Agency of the Czech Technical University in Prague, grant No. SGS10/221/OHK2/2T/16.